To Analyze Thrill, Define Extreme Sports - Buckley, Ralf C. (Frontiers in Psychology, 2018)
Emotions are a signalling system, evolved by providing selective advantage through enhanced survival and reproduction. The selective advantage conferred by thrill or exhilaration, however, remains unknown. Hypotheses, as yet untested, include overcoming phobias or honing physical skills as juveniles, or exhibiting desirability during mate selection. Extreme sports can provide an ethically and experimentally feasible tool to analyse thrill. To use this tool, extreme sports must first be defined in a non-circular way, independent of participant psychology. Existing concepts, from different disciplines, focus respectively on drama, activity types, or consequences of error. Here I draw upon academic and popular literature, and autoethnographic experience, to distinguish extreme from adventurous levels for a range of different outdoor sports. I conclude that extreme outdoor adventure sports can be defined objectively as those activities, conditions, and levels, where participant survival relies on moment-by-moment skill, and any error is likely to prove fatal. This allows us to examine the motivations, experiences, and transformations of individuals who undertake these activities. In particular, it will allow us to examine the emotional experience of thrill, previously studied principally as an aspect of personality, from new neurophysiological and evolutionary perspectives.